Crystallochemistry of defects in lead telluride films - Freik, D.M.; Ruvinskii, M.A.; Ruvinskii, B.M.; Galushchak, M.A. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2001)
The crystallochemical model of vapor-phase epitaxy of the lead telluride films has been proposed with the supposition about the simultaneous formation of singly charged, doubly charged and electroneutral Frenkel defects in the cationic sublattice. It has been shown that in spite of the large concentration of partly compensated doubly charged defects the singly charged Frenkel pairs Pbi⁺ and VPb⁻ also play an essential role in change carrier concentration in PbTe films. The results of numerical calculation agree with the available experimental data of the dependence of charge carrier's concentration in films upon the partial pressure of tellurium vapor and the deposition's temperature in the hot-wall method.